LANGUAGE APPRAISAL ON ATTITUDINAL SYSTEMS FOR EXPLORING IDEOLOGY IN DEATH PENALTY IN SYDNEY MORNING HERALD AND HERALD SUN EDITORIALS - Rosyida Ekawati (Humaniora, 2015)
This article deals with the ideology represented by newspaper editorials. It is from the idea that every language use is never neutral and not ideology-free. Language is used to convey meanings in a broad sense. There are meanings related to the opinions through the language as resources of evaluation. Editorial is one practice of language use full of opinions towards a certain issue on people or things. Sydney Morning Herald and Herald Sun are used as both Australian newspaper posit themselves as the high-rank newspaper in terms of circulation and online accessed. This article tries to uncover the ideologies represented by both newspaper editorials concerning death penalty of Bali Nine executed in Indonesia. Attitudinal perspective proposed by Martin and White (2005) in term of affect, judgement, and appreciation of language appraisal is used to explore ideology in the newspaper. From appraisal analysis, it is found that Indonesia dominantly appraised in negative There is no positive appreciation for Indonesia in both newspaper editorials. judgement while Australia is portrayed in positive view for the issue of death penalty in Indonesia.